Successful scale-up of human embryonic stem cell production in a stirred microcarrier culture system - Fernandes,A.M. (2009)
Future clinical applications of human embryonic stem (hES) cells will require high-yield culture protocols. Currently, hES cells are mainly cultured in static tissue plates, which offer a limited surface and require repeated sub-culturing. Here we describe a stirred system with commercial dextran-based microcarriers coated with denatured collagen to scale-up hES cell production. Maintenance of pluripotency in the microcarrier-based stirred system was shown by immunocytochemical and flow cytometry analyses for pluripotency-associated markers. The formation of cavitated embryoid bodies expressing markers of endoderm, ectoderm and mesoderm was further evidence of maintenance of differentiation capability. Cell yield per volume of medium spent was more than 2-fold higher than in static plates, resulting in a significant decrease in cultivation costs. A total of 10(8) karyotypically stable hES cells were obtained from a unitary small vessel that needed virtually no manipulation during cell proliferation, decreasing risks of contamination. Spinner flasks are available up to working volumes in the range of several liters. If desired, samples from the homogenous suspension can be withdrawn to allow process validation needed in the last expansion steps prior to transplantation. Especially when thinking about clinical trials involving from dozens to hundreds of patients, the use of a small number of larger spinners instead of hundreds of plates or flasks will be beneficial. To our knowledge, this is the first description of successful scale-up of feeder- and Matrigel™-free production of undifferentiated hES cells under continuous agitation, which makes this system a promising alternative for both therapy and research needs.